Role of free volume in mechanical behaviors of side chain lcp grafted products of high density polyethylene - YAHŞİ, UĞUR (SPRINGER, 2021)
The monomer, p-benzophenoneoxycarbonylphenyl methacrylate (BPOCPMA) the polymer of which exhibit mesomorphic behavior as side chain LCP has been graft copolymerized onto high density polyethylene (HDPE) in order to improve its properties. The PALS analysis of the products displayed that the graft copolymerization, while led to relatively small increase in the free volume size at low percentages of poly(BPOCPMA), resulted in decreases in the size and fraction of the free volume with the increase of poly(BPOCPMA) content. The graft copolymerization gave rise to remarkable improvements in the mechanical properties, especially in tensile strength and modulus, and the improvements were accompanied by the decreases in the free volume fraction. SEM analysis of the fracture surfaces of the mechanical test samples displayed a gradual transition from ductile fracture at low graft contents to brittle nature dominated at high percentages of poly(BPOCPMA). The XRD analysis showed significant expansions in the lateral dimensions (a and b parameters) of the orthorhombic unit cell in the crystalline domains of HDPE matrix, in consistence with poly(BPOCPMA) content. The grafting also gave rise to noteworthy increases in the crystalline melting temperature of the HDPE.
Keywords: Grafting; Copolymers; Morphology; Free volume; Mechanical properties; X-RAY-SCATTERING; IN-SITU SAXS; SEMICRYSTALLINE POLYMERS; POSITRON-ANNIHILATION; CRYSTALLINE POLYMERS; TENSILE DEFORMATION; PLASTIC-DEFORMATION; MOLECULAR TOPOLOGY; CAVITATION; POLYPROPYLENE